2012
DOI: 10.3748/wjg.v18.i44.6427
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic role of 18F-fluorodeoxyglucose positron emission tomography for follicular lymphoma with gastrointestinal involvement

Abstract: AIM:To investigate the capacity for 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET) to evaluate patients with gastrointestinal lesions of follicular lymphoma. METHODS:This retrospective case series consisted of 41 patients with follicular lymphoma and gastrointestinal involvement who underwent 18F-FDG-PET and endoscopic evaluations at ten different institutions between November 1996 and October 2011. Data for endoscopic, radiological, and biological examinations performed were retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…The frequent absence of CT findings may be explained by the small size of the lesions. FDG PET also is not a reliable imaging tool, with a sensitivity of 46% for detecting GI follicular lymphoma (54). This high false-negative rate is likely related to the small size of the GI lesions, as well as the lower avidity of GI follicular lymphoma at FDG PET compared with more aggressive forms of lymphoma (54).…”
Section: Follicular Lymphomamentioning
confidence: 95%
See 1 more Smart Citation
“…The frequent absence of CT findings may be explained by the small size of the lesions. FDG PET also is not a reliable imaging tool, with a sensitivity of 46% for detecting GI follicular lymphoma (54). This high false-negative rate is likely related to the small size of the GI lesions, as well as the lower avidity of GI follicular lymphoma at FDG PET compared with more aggressive forms of lymphoma (54).…”
Section: Follicular Lymphomamentioning
confidence: 95%
“…Imaging Features.-GI follicular lymphomas are manifested at barium studies and CT by multiple small-bowel nodules of varying size (53). In one retrospective study, however, Iwamuro (54) found that only 15% of patients with GI involvement by follicular lymphoma had abnormal GI findings at CT, with a thickened bowel wall in all cases (Fig 10). The frequent absence of CT findings may be explained by the small size of the lesions.…”
Section: Follicular Lymphomamentioning
confidence: 97%
“…As a result, response to therapy of lymphomatous deposits lodging in the bone marrow cannot be assessed using FDG-PET. The same applies to the gastrointestinal tract, since studies have shown that FDG-avidity is absent in large proportions of patients with biopsy-proven intestinal involvement [19,20].…”
Section: Letter To the Editormentioning
confidence: 99%
“…Patients with grade 3 follicular lymphoma were excluded from this study because these cases are typically managed as cases of diffuse large B-cell lymphoma (1). A subset of the 12 patients examined herein were also subjects of our previous studies (4,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Methodsmentioning
confidence: 99%